A case of problematic internet use successfully treated with an SSRI-antipsychotic combination - Atmaca, Murad (Pergamon-Elsevier Science Ltd, 2007)
[Abstract Not Available]
Keywords: Obsessive-Compulsive Disorder; Augmentation; Quetiapine